2013
DOI: 10.2169/internalmedicine.52.9522
|View full text |Cite
|
Sign up to set email alerts
|

Slowly Progressive Type 1 Diabetes Treated with Metformin for Five Years after Onset

Abstract: A 52-year-old man was diagnosed with slowly progressive type 1 diabetes (SPIDDM). We expected him to quickly progress to an insulin-dependent state due to a high anti-glutamic acid decarboxylase antibody titer (23.9 U/mL). At SPIDDM diagnosis, he was in a non-insulin-dependent state, with a fasting serum C-peptide immunoreactivity level of 2.5 ng/mL. Therefore, we prescribed metformin. His glycemic control remained stable, and his intrinsic insulin secretion capacity was maintained for five years. Although one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Metformin was used to treat five of the six patients in the S group at baseline; during the study period, the dosage was increased in two patients and was added in one patient (Table S2). We previously reported that metformin may suppress the disease course of SPIDDM/LADA more effectively than pioglitazone [ 23 ], and we subsequently experienced a patient with SPIDDM/LADA whose β-cell function was maintained for 5 years with treatment of metformin alone [ 37 ]. Metformin increases the GLP-1 level [ 38 ], which regulates lymphocyte proliferation and the maintenance of peripheral regulatory T cells [ 39 ]; given that metformin was recently reported to improve gut microbiome flora in type 2 diabetes patients [ 40 ], metformin treatment for non-insulin-dependent SPIDDM might have exerted immunomodulatory effects through gut flora modification.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin was used to treat five of the six patients in the S group at baseline; during the study period, the dosage was increased in two patients and was added in one patient (Table S2). We previously reported that metformin may suppress the disease course of SPIDDM/LADA more effectively than pioglitazone [ 23 ], and we subsequently experienced a patient with SPIDDM/LADA whose β-cell function was maintained for 5 years with treatment of metformin alone [ 37 ]. Metformin increases the GLP-1 level [ 38 ], which regulates lymphocyte proliferation and the maintenance of peripheral regulatory T cells [ 39 ]; given that metformin was recently reported to improve gut microbiome flora in type 2 diabetes patients [ 40 ], metformin treatment for non-insulin-dependent SPIDDM might have exerted immunomodulatory effects through gut flora modification.…”
Section: Discussionmentioning
confidence: 99%
“…Candidates for combination treatment for preserving beta cell function in SPIDDM include metformin,12 which changes gut microbiota profiles, and pioglitazone, although results are inconclusive 109,110…”
Section: Prevention Strategies and Clinical Options For Spiddmmentioning
confidence: 99%